Founded in fiction : the uses of fiction in the early United States - Koenigs, Thomas, 1985- (Princeton University Press, 2021)
"This monograph presents a new history of early American literature that traces the diverse forms of fiction circulating in the early United States (1789-1861) and how they shaped the way Americans thought and argued about political and cultural issues of their age"--